Menangani Konflik dengan Etika dan Rofesionalisme dalam Komunikasi Bisnis: Literatur Review - Muhammad Dwi Arif (Jurnal Pendidikan Manajemen Transportasi, 2023)
Conflict in the business world is like an inevitable fire. This fire, if not extinguished with ethics and professionalism in business communication, can burn the entire organization and hinder success. This study reveals the importance of ethics and professionalism in dealing with conflict. Ethics and professionalism are like the air that cools the fire, helping to build constructive, fair, and respectful communication. With good communication, conflict can be resolved in an optimal way that benefits all parties. Strategies for resolving the fire of conflict are also diverse. Staying calm and professional, listening attentively, and focusing on solutions are key. Compromising and asking for help when needed are also equally important. The principles of communication ethics serve as a compass in guiding steps. Honesty, fairness, confidentiality, and accountability are like solid pillars that support ethical communication. The positive impact of proper conflict handling is like flowers blooming in a garden. Increased productivity, efficiency, communication quality, and cooperation are real evidence. Innovation and creativity thrive, employee retention increases, and the company's reputation shines. Case examples and conclusions are real illustrations of how ethics and professionalism help resolve the fire of conflict in the business world. Ethics and professionalism are like heroes who save organizations from destruction and lead them to success.